Experience of mothers after the diagnosis of congenital malformation and the expectations of care - Ana Cláudia Monzon Zampoli; Sebastião Caldeira; Karine Brito dos Santos; Oscar Kenji Nihei; Rosane Meire Munhak da Silva (Universidade Federal do Ceará, 2022)
Objective: to understand the experience of mothers after the diagnosis of congenital malformation and the expectations of care from the health and social network. Methods: qualitative research based on Social Phenomenology, with the participation of six mothers living in border towns, by means of semi-structured interviews. Results: the reports brought information about the diagnosis of congenital malformation, the experience of pregnancy, becoming a mother of a child with malformation and the expectations of health and social care. Conclusion: the social group studied experienced the diagnosis of malformation with suffering, emotional repercussions and changes in their daily lives. Contributions to practice: communication by the health team contributes to understanding and facing the malformation. The importance of the family and social network support was highlighted. It is necessary to develop professional skills related to communication and to make more investments in training and working conditions that allow more time for the care of this public.